Celebrating Our Progress and Charting the Path Forward (OCEM Journal of Management, Technology & Social Sciences, 2024)
This editorial aims to reflect on the significant milestones achieved by the OCEM Journal of Management, Technology & Social Sciences over the past year, particularly highlighting the successful conclusion of the inaugural OCEM International Conference on Green Technology and Talent Management.The editorial outlines the key accomplishments of the journal, including the hosting of the conference on May 10th and 11th, 2024, which served as a platform for interdisciplinary dialogue among scholars, industry leaders, and practitioners focused on sustainability and organizational excellence.The conference resulted in the presentation of forty-five research papers, from which fifteen high-quality articles were selected for publication in a special volume of the journal. This event marked a pivotal moment for the journal, bridging the gap between research and practical application in the fields of green technology and talent management.The editorial discusses future initiatives aimed at enhancing the journal's quality, including ongoing commitments to open access and impactful research, thereby fostering scholarly discourse and advancing academic excellence.By documenting these achievements and future plans, this editorial contributes to the understanding of the journal's role in promoting interdisciplinary research and its dedication to sustainability and innovation in management practices.